RATIONAL DESIGN OF AUTOMATIC FIRE EXTINGUISHING FOR SKYSCRAPERS - Чернецкая, И. В.; Истомина, О. С.; Полищук, А. В. (Academic journal Industrial Machine Building Civil Engineering, 2017)
As a result of investigations the constructive decisions that make it possible to increase efficiency and reliability of the automatic fireextinguishing systems of high rise buildings with glass facades and provide the material resources saving were developed. Keywords:high rise building, skyscraper, fire extinguishing, automatic fire extinguishing system, sprinkler.